ANALISIS SISTEM PENGENDALIAN INTERNAL SIKLUS PENGGAJIAN PADA CV.X - WAHYU PUTRANTO, HENDI (Jurnal Akuntansi AKUNESA, 2015)
This research is describing about the implementation of the payroll system in CV.X. The purpose of this research is to know the internal control system in companies as well as perform analysis compared the way the fellowship system that runs with payroll accounting information systems theory. This study uses qualitative methods with qualitative descriptive research approach. And the results showed that the system of internal control in companies is still very weak, since the internal control system theory, many of which are not applied by the company. so companies need to conduct an evaluation or planed back a good internal control system in the company. Keyword: internal control system, Payroll Systems